Synthesis, characterization, and fluorescence phenomena of 1-naphthoxy and 1-naphthylamino substituted cyclotriphosphazenes - Aslan, Fatih; Halci, Oguzhan; Arslan, Mustafa (Wiley-Hindawi, 2008)
The reactions of hexachlorocyclotriphosphazene N3P3Cl6 (1) with 1-naphthol and 1-naphthylamine have been examined. The reaction of 1 with sodium 1-naphthoxy gave the hexakis(I-naphthoxy)cyclotriphosphazene (2) in high yield. Geminal 2,2-di(1-naphthylamino)-4,4,6,6-tetrachlorocyclotriphosphazene (3) was obtained from the reaction of I with 1-naphthylamine. The structures of phosphazene derivatives were defined by elemental analysis, FTIR, UV-visible, and H-1, C-13, P-31 NMR spectroscopy. The fluorescence intensity of the compounds was measured in THF and CH2 Cl-2. (C) 2008 Wiley Periodicals, Inc.
Keywords: P-31 Nmr; Polyphosphazenes